2015
DOI: 10.1371/journal.pone.0124497
|View full text |Cite|
|
Sign up to set email alerts
|

De Novo Transcriptome Analysis to Identify Anthocyanin Biosynthesis Genes Responsible for Tissue-Specific Pigmentation in Zoysiagrass (Zoysia japonica Steud.)

Abstract: Zoysiagrass (Zoysia japonica Steud.) is commonly found in temperate climate regions and widely used for lawns, in part, owing to its uniform green color. However, some zoysiagrass cultivars accumulate red to purple pigments in their spike and stolon tissues, thereby decreasing the aesthetic value. Here we analyzed the anthocyanin contents of two zoysiagrass cultivars ‘Anyang-jungji’ (AJ) and ‘Greenzoa’ (GZ) that produce spikes and stolons with purple and green colors, respectively, and revealed that cyanidin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 45 publications
4
25
0
Order By: Relevance
“…Figure 3C shows homologies with plants in the family Poaceae. Recent research (Ahn et al, 2015 ) supports our data showing that the most homologous model species to Zoysia is Setaria itallica , followed by Sorghum bicolor and Zea mays . Due to the differences in tissue between cultivar and treatment, our results were not completely consistent with that research.…”
Section: Resultssupporting
confidence: 87%
“…Figure 3C shows homologies with plants in the family Poaceae. Recent research (Ahn et al, 2015 ) supports our data showing that the most homologous model species to Zoysia is Setaria itallica , followed by Sorghum bicolor and Zea mays . Due to the differences in tissue between cultivar and treatment, our results were not completely consistent with that research.…”
Section: Resultssupporting
confidence: 87%
“…6), including two chalcone synthase (CHS), two chalcone isomerase (CHI), two flavanone 3-hydroxylase (F3H), five flavonoid 3'-hydroxylase (F3'H), two flavonoid 3',5'-hydroxylase (F3’5’H), four dihydroflavonol 4-reductase (DFR), four anthocyanidin synthase (ANS) and seven UDP-glucose flavonoid glucosyl transferase (UFGT). Aspects of the above ratios corroborate prior studies that have found comparatively high copy numbers for DFR ( Lotus japonicus [43]; cherries [44]; red leaf lettuce [45]), UFGT (columbines [46]; cherries [44]; Stellera chamaejasme [47]), F3H (peonies [48]), and ANS ( Zoysia [49]). Similarly, our finding of a low copy number for F3'5'H corroborates data from the above studies (one prominent exception is grapevines, which have been found to have exceptionally high copy variants of this enzyme [50]).…”
Section: Resultssupporting
confidence: 87%
“… 8 In parallel with the construction of genetic maps, transcriptome analyses have been used to identify abiotic stress-related genes 9 , 10 and genes that control tissue-specific anthocyanin pigmentation in Z. japonica . 11 A complete sequence of the chloroplast genome of Z. matrella L. Merr has also been published. 12 …”
Section: Introductionmentioning
confidence: 99%